Supply Chain optimization with two echelons in a small medium enterprise printing company - Cardenas Yupanqui, Betsy Juistin (2024)
This paper shows an optimized supply chain of a small-medium enterprise (SME) printing company. The methodology used was divided into two phases: phase I: identification of the current scenario and input analysis, and Phase II: implementation of the model with the application of Python, in which results were obtained from the optimization of the production plan, inventory plan, sales, plan and maintenance plan. With the validation of the software, a maximization was obtained with a profit of $58,113 per year. In addition to the modeling, it is possible to find the number of products to be produced in the following months of the year; that is to say, it is possible to foresee the number of inputs necessary to supply the company's demand.